Il diritto all’obiezione di coscienza all’aborto nel Regno Unito. Nota a Greater Glasgow Health Board v. Doogan and another [2014] UKSC 68 (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
In its Doogan judgment of 17 December 2014 the UK Supreme Court expressed its view on the scope of the right of conscientious objection granted by section 4 of the Abortion Act 1967. The Court maintained that conscientious objectors are only exempted from “hands-on” participation in an abortion and not from managerial tasks and general nursing care. The judgment is in line with the general trend of other supreme or constitutional courts in Europe that supports a narrow interpre-tation of conscience-based exemptions in abortion laws. This judgment’s distinguishing feature is its technical approach, aimed at deciding what the Abortion Act’s section means “according to the ordinary principles of statutory construction”, without speculating on the broader consequences of taking a wide or a narrow view of this section. Still the Court’s narrow interpretation is counterbalanced by the statement that, even if not protected by the Abortion Act’s conscience clause, the petitioners’ right of conscientious objection can nevertheless be claimed either under the Human Rights Act or under the Equality Act, according to the specific context of the petition.
Keywords: Conscientious objection; Abortion Act 1967; Midwife; Participation in treatment; Human Rights Act